Роман, який не вдалося “спалити” (до питання рецепції “Собору” О. Гончара) - Тетеріна, О. (Слово і Час, 2018)
У статті проаналізовано рецепцію “Собору” О. Гончара з огляду на різні її аспекти як в Україні,
так і в діаспорі (Ю. Бойко, В. Дончик, І. Кошелівець, Д. Павличко, А. Погрібний, Л. Рудницький,
Є. Сверстюк, Г. Тютюнник, Ю. Шерех).
Крізь призму сприйняття твору насамперед Ю. Бойка (його стаття “Спалений роман” – один
із перших відгуків на твір Гончара в діаспорі – майже невідома та не оприлюднена в Україні)
осмислено функціональність “Собору” в тогочасному розвиткові української літератури,
нерозривно (!) пов'язаному з соціокультурним життям. The paper considers reception of O. Honchar’s novel “The Cathedral” (“Sobor”) taking into account its
controversial manifestations, both in Ukraine and in the diaspora (Y. Boyko, V. Donchyk, I. Koshelivets,
D. Pavlychko, A. Pohribnyi, L. Rudnytskyi, Y. Sverstiuk, G.Tiutiunnyk, Y. Sherekh).
The functional role of “The Cathedral” in the development of the national literature, then inseparably
linked with the social life of Ukraine, is conceptualized, first of all, based on Y. Boyko’s ideas (whose
article “Incinerated Novel”, one of the first reviews on this Honchar’s book in the diaspora, remained
unknown in Ukraine until now).
Th e researchers’ opinion of this novel as a ‘culmination’ of the writer’s creative work is actualized
considering its powerful nation-building role, and, at the same time, a special attention of the writer,
who was a representative of ‘poetic realism’ (A. Pohribnyi) in the Ukrainian literature, to such national
spiritual values as native language, culture and history. There is an internal connection of the symbolic
images of the cathedral (“The Cathedral”) and the Mother of God (“Your Star”) with the author’s thoughts
about the fate of his people on a ‘planetary scale’ running through all his literary work.
It is stated that O. Honchar’s novel “The Cathedral”, while promoting national literary tradition,
rises to the highest level in comprehension of universal human problems, remaining nevertheless
deeply rooted in its Ukrainian ground and promoting national literary tradition. This ‘universal piece
of art’ (L. Rudnytskyi) is still extremely relevant and serves as ‘a tower of strength’ (Y. Sverstiuk) for
spirituality of the nation. В статье проанализирован вопрос рецепции
романа “Собор” О. Гончара, учитывая разные ее аспекты как в Украине, так и в диаспоре
(Ю. Бойко, В. Дончик, И. Кошеливец, Д. Павлычко, А. Погрибный, Л. Рудныцкий, Е. Сверстюк,
Г. Тютюннык, Ю. Шерех). Сквозь призму восприятия прежде всего
Ю. Бойка (его статья “Сожженный роман” – один из первых отзывов на произведение Гончара в
диаспоре – почти неизвестна и не напечатана в Украине) осмыслена функциональность “Собора”
в развитии украинской литературы, неразрывно связанном в то время с социокультурной жизнью.